Employee acceptance of digital monitoring systems while working from home - Luisa Wieser; Martin Abraham (New Technology, Work and Employment, 2023)
Digitalisation and COVID-19 led to an expansion of remote work arrangements, raising the question of whether and how employers should monitor remote workplaces. However, before the implementation of monitoring methods, it is important to consider employees' acceptance of this approach. Therefore, we contribute to current research on electronic performance monitoring by empirically investigating employees' evaluations of performance monitoring at home. This paper presents an analysis of how certain monitoring technologies for work-from-home arrangements are perceived as undesirable and whether other job aspects can compensate for these unattractive monitoring components. Using an experimental factorial survey design, German employees evaluated remote work arrangements with randomly varying characteristics. We show that respondents accept a certain degree of monitoring at home but increasingly reject monitoring systems as they become more invasive. However, in some cases, the negative impact of monitoring at home can be mitigated by certain incentives, such as money or the purpose of monitoring.
Keywords: 330; electronic performance monitoring; employee attitudes; employee monitoring; experimental survey design; privacy concerns; remote work; social exchange theory